A Comparative Analysis of Competitive Balance Between a Closed and an Open League in Rugby League. (December 2021) - Read, Daniel; Smith, Aaron C.T.; Skinner, James
League regulators aim for an equitable competition where each team has an equal chance of winning the championship, termed competitive balance. It is generally assumed that closed leagues with stricter labor market regulations should demonstrate better competitive balance than open leagues with promotion and relegation. The aim of this research was to examine the competitive balance between and within seasons in the closed Australian National Rugby League (NRL) and open English Super League using five measures of concentration and dominance. Overall, the closed NRL competition demonstrated superior competitive balance. The practical and theoretical implications of the findings are discussed.